2011
DOI: 10.4236/scd.2011.13005
|View full text |Cite
|
Sign up to set email alerts
|

Endodermal progenitor cells isolated from mouse pancreas

Abstract: In this study we have isolated and identified a progenitor cell population located in murine pancreatic tissue. This cell population has specific properties that make it different from previously described candidate pancreatic progenytor cell populations. It is located in the periductal region outside the islet architecture yet the cells have features consistent with endodermal development and endocrine functions within the islet. Cells are proliferative and capable of differentiation into pancreatic lineages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Progenitors isolated from mice are found to bear several surface markers. For instance, Samuelson et al [37], showed that the highly proliferative pancreatic progenitor population isolated from mice has been found to express stem cells antigen 1- (Sca-1). Another study showed the presence of Nestin positive multipotent progenitor cells in the centrilobular ducts of the adult rat pancreas [38].…”
Section: Origin Of Pancreatic Cancer Stem Cell Hypothesismentioning
confidence: 99%
“…Progenitors isolated from mice are found to bear several surface markers. For instance, Samuelson et al [37], showed that the highly proliferative pancreatic progenitor population isolated from mice has been found to express stem cells antigen 1- (Sca-1). Another study showed the presence of Nestin positive multipotent progenitor cells in the centrilobular ducts of the adult rat pancreas [38].…”
Section: Origin Of Pancreatic Cancer Stem Cell Hypothesismentioning
confidence: 99%
“…Determined stem cells for pancreatic cell therapies have not been considered an option based on evidence that there are no or only rare pancreatic stem cells in postnatal tissues []. The few studies in which OCT4 + and SOX2 + multipotent stem cells have been identified in adult pancreas have indicated also their rarity []. Instead, the postnatal pancreas has long been thought to contain only committed progenitors, found in pancreatic ducts [] and, more recently, in pancreatic duct glands (PDGs) by Thayer and associates [].…”
Section: Introductionmentioning
confidence: 99%